The potential effects of IFRS for SMEs on New Zealand SME financial reporting - Morunga, Maria (Massey University, 2010)
No abstract
Research report (M.B.S.), Massey University, Palmerston North, 2010
Keywords: International Financial Reporting Standards; Financial statements; Small business; Business accounting